2019
DOI: 10.1002/jcb.28971
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of neuroprotective activity of digoxin and semisynthetic derivatives against partial chemical ischemia

Abstract: Recently, cardiotonic steroids (CTS) have been shown to lead to the activation of Na,K‐ATPase at low concentrations in brain, promoting neuroprotection against ischemia. We report here the results of the use of digoxin and its semisynthetic derivatives BD‐14, BD‐15, and BD‐16 against partial chemical ischemic induction followed by reperfusion in murine neuroblastoma cells neuro‐2a (N2a). For chemical ischemic induction, sodium azide (5 mM) was used for 5 hours, and then reperfusion was induced for 24 hours. Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 63 publications
0
4
0
3
Order By: Relevance
“…Thus, in addition to expanding knowledge about signaling pathways and neuroprotective effects of low doses of ouabain and other cardiotonic, a strategy for the safe therapeutic use of cardiotonic steroids for neuroprotection would be the chemical modification of their structure to increase the therapeutic index of this class. Gamma-benzylidene digoxin derivatives are digoxin-derived molecules that have demonstrated low toxicity to cells ( de Oliveira et al, 2021 ) and have already demonstrated neuroprotection for chemical ischemia ( de Souza Gonçalves et al, 2019 ) and increased α3 activity and increased antioxidant defenses such as GSH, desired drug characteristics of neuroprotection ( Parreira et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in addition to expanding knowledge about signaling pathways and neuroprotective effects of low doses of ouabain and other cardiotonic, a strategy for the safe therapeutic use of cardiotonic steroids for neuroprotection would be the chemical modification of their structure to increase the therapeutic index of this class. Gamma-benzylidene digoxin derivatives are digoxin-derived molecules that have demonstrated low toxicity to cells ( de Oliveira et al, 2021 ) and have already demonstrated neuroprotection for chemical ischemia ( de Souza Gonçalves et al, 2019 ) and increased α3 activity and increased antioxidant defenses such as GSH, desired drug characteristics of neuroprotection ( Parreira et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For this measurement [ 43 ], changes of absorption in the presence of 50 μl of supernatant and 250 μl of phosphate buffer solution (50 mM, pH 7.4) containing NaN₃ (1.25 mM), ethylenediaminetetraacetic acid (EDTA, 4 mM), H 2 O 2 (0.25 mM), GSH (1 mM), and nicotinamide adenine dinucleotide phosphate cofactor (NADPH, 0.16 mM) were read at 365 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Many CGs have already been synthesized with changes in the lactone ring, in the steroidal nucleus and in the sugar moiety 4–7 . It has been reported that the number and positions of the hydroxyl groups present in the steroid nucleus affect the interaction with Na + /K + ‐ATPase 3 .…”
Section: Introductionmentioning
confidence: 99%
“…3 Many CGs have already been synthesized with changes in the lactone ring, in the steroidal nucleus and in the sugar moiety. [4][5][6][7] It has been reported that the number and positions of the hydroxyl groups present in the steroid nucleus affect the interaction with Na + /K + -ATPase. 3 Kanai et al, 8 raise the possibility of conferring α2 specificity by steroid core modifications that favor the formation of hydrogen bonds with Ser119 in α2.…”
Section: Introductionmentioning
confidence: 99%